What are people eating in Rangpur, Bangladesh? Food consumption, food security, food sources, and food perceptions - Scott, Samuel P.; Patwardhan, Sharvari; Chakrabarti, Suman; Chauhan, Alka; Banerjee, Archis; Neupane, Sumanta; Parvin, Aklima; Rasheed, Sabrina; Afsana, Kaosar; Shaheen, Nazma; Blake, Christine; Menon, Purnima; et al. (CGIAR, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a district-level multi year assessment. Using data collected in February– March 2023, this data note describes what people are eating, where they get their food, household food insecurity, and perceptions about food. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.